The Warburg Effect: 80 years on - Morten, K; Potter, M; Newport, E (Portland Press, 2016)
Influential research by Warburg and Cori in the 1920’s ignited interest in how cancer cells’ energy generation is different to normal cells’. They observed high glucose consumption and large amounts of lactate excretion from cancer cells compared to normal cells which oxidised glucose using mitochondria. It was therefore assumed that cancer cells were generating energy using glycolysis rather than mitochondrial oxidative phosphorylation and that the mitochondria were dysfunctional. Advances in research techniques since then have shown the mitochondria in cancer cells to be functional across a range of tumour types. However, different tumour populations have different bio-energetic alterations in order to meet their high energy requirement; the Warburg effect is not consistent across all cancer types. This review will discuss the metabolic reprogramming of cancer, possible explanations for the high glucose consumption in cancer cells observed by Warburg and suggest key experimental practices we should consider when studying the metabolism of cancer.